Expressive Suppression and Negative Affect, Pathways of Emotional Dysregulation in Psoriasis Patients - Ciuluvica, Cristina; Fulcheri, Mario; Amerio, Paolo (Frontiers in Psychology, 2019)
The main goal of this study was to assess the emotion regulation (ER) mechanisms such as expressive suppression and cognitive reappraisal in patients with psoriasis as compared with healthy persons not afflicted by dermatological diseases. Moreover, the study intended to carry on a multidimensional assessment of emotional mechanisms in persons with psoriasis, highlighting the differences between psoriasis patients and healthy participants, in order to identify the specific patterns of emotion dysregulation (ED) in psoriasis. Another goal of the study was to investigate the predictors of ED among different emotional patterns. We presumed that the maladaptive ER mechanisms are higher in psoriasis patients than in control group and there are specific dysregulation patterns in psoriasis patients as negative emotions tendency. This cross-sectional study was performed on 192 individuals aged between 35 - 75 years (mean age 59). The sample was divided in two groups: the clinical group including 91 patients with a diagnosis of psoriasis vulgaris, and the control group including 101 healthy persons. The results of the present study suggest that psoriasis patients used more frequently emotional suppression - a maladaptive ER mechanism – as well as ED patterns – i.e., impulse control difficulties, and nonacceptance of emotional responses. They also displayed trait tendency to a negative emotional response. In fact, in people with psoriasis the presence of suppression mechanism and negative affect of trait could predict that 35 % of patients will show emotional dysregulated patterns, living with higher levels of ED. The results of our study are important in the clinical practice helping clinicians to better understand the emotional vulnerability of people that live with psoriatic disease, and to optimize the disease management and patient care in an interdisciplinary approach.